2014
DOI: 10.1039/c4sm01722f
|View full text |Cite
|
Sign up to set email alerts
|

Structure factor of blends of solvent-free nanoparticle–organic hybrid materials: density-functional theory and small angle X-ray scattering

Abstract: We investigate the static structure factor S(q) of solvent-free nanoparticle-organic hybrid materials consisting of silica nanocores and space-filling polyethylene glycol coronas using a density-functional theory and small angle X-ray scattering measurements. The theory considers a bidisperse suspension of hard spheres with different radii and tethered bead-spring oligomers with different grafting densities to approximate the polydispersity effects in experiments. The experimental systems studied include pure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 27 publications
2
52
1
Order By: Relevance
“…polymers and moderately branched star polymer melts are more closely related in their configurational and thermodynamic properties, as well as to ring polymer melts, than linear chain melts [33,40]. Similar suppression of density fluctuations has been observed in the packing of polymer-grafted nanoparticles in the absence of solvent, a novel type of materials that several studies demonstrated their have special properties related to hybrid character of the particles and the highly uniform packing configurations that these particles exhibit [41][42][43]. It is evident that branched molecules exhibit non-trivial correlations in their molecular packing and hyperuniformity can provide a valuable tool to probe these correlations.…”
Section: Total Correlationsmentioning
confidence: 67%
“…polymers and moderately branched star polymer melts are more closely related in their configurational and thermodynamic properties, as well as to ring polymer melts, than linear chain melts [33,40]. Similar suppression of density fluctuations has been observed in the packing of polymer-grafted nanoparticles in the absence of solvent, a novel type of materials that several studies demonstrated their have special properties related to hybrid character of the particles and the highly uniform packing configurations that these particles exhibit [41][42][43]. It is evident that branched molecules exhibit non-trivial correlations in their molecular packing and hyperuniformity can provide a valuable tool to probe these correlations.…”
Section: Total Correlationsmentioning
confidence: 67%
“…Hsiu‐Yu and Koch first argued that GNP materials in the absence of solvent should have small long‐wavelength density fluctuations, and this effect has already been confirmed by experiments and molecular dynamics simulations (for an overview of these materials see the following reviews ). If these density fluctuations are sufficiently suppressed, then a hyperuniform material can be expected.…”
Section: Introductionmentioning
confidence: 91%
“…57,58 In particular, the strong chain mediated correlations among the core particles lead to higher primary peaks, while the space filling constraint suppresses concentration fluctuations and results in a more rapid decay and lower S values in the low q regime. 57,58 In particular, the strong chain mediated correlations among the core particles lead to higher primary peaks, while the space filling constraint suppresses concentration fluctuations and results in a more rapid decay and lower S values in the low q regime.…”
Section: Resultsmentioning
confidence: 99%